2020
DOI: 10.1101/2020.04.26.062380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parkinson Disease-Linked Parkin Mediates Redox Reactions That Lower Oxidative Stress In Mammalian Brain

Abstract: We recently hypothesized that parkin plays a role in redox homeostasis and provided evidence that it directly reduces hydrogen peroxide (H 2 O 2 ) in vitro. Here, we examined this anti-oxidant activity in vivo. Informed by findings in human brain, we demonstrate that elevated oxidative stress promotes parkin insolubility in mice. In normal mouse brain parkin was partially oxidized, e.g., at cysteines 195 and 252, which was augmented by oxidative stress. Although under basal conditions H 2 O 2 levels were uncha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 58 publications
2
12
4
Order By: Relevance
“…2h,i ). Of note, in both models we confirmed the rise in H 2 O 2 levels (see below and El Kodsi et al [38]). In contrast to murine parkin, the solubility of endogenous Dj-1, encoded by a second, ARPD-linked gene, was not visibly affected on SDS/PAGE under these elevated oxidative stress conditions ( Fig.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…2h,i ). Of note, in both models we confirmed the rise in H 2 O 2 levels (see below and El Kodsi et al [38]). In contrast to murine parkin, the solubility of endogenous Dj-1, encoded by a second, ARPD-linked gene, was not visibly affected on SDS/PAGE under these elevated oxidative stress conditions ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…Such changes could profoundly affect parkin function mediated by other domains, as has been shown in several studies involving its E3 ligase activity as a readout following modifications in the UbL domain [27, 29-31, 34, 55, 74-76] (and reviewed in Yi et al [77]). Our results do not exclude the possibility that other non-thiol-based, posttranslational modifications alter parkin solubility, such as phosphorylation at Ser65 [78], or at Ser77 [38], which we found in MPTP-treated murine brain (not shown).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Lee et al recently reported that Parkin can also undergo methionine oxidation at M192, a residue mutated in early onset Parkinson's [ 301 ], and that this is reversed by methionine sulfoxide reductase B2 (MSRB2) released in response to damaged mitochondria, thereby promoting mitophagy [ 302 ]. Finally, El Kodsi et al have reported that Parkin can be glutathionylated in an antioxidant reaction (at preprint stage at the point of writing this review) [ 303 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%